Understanding Halal Food Consumption: A Systematic Literature Review of Theoretical Frameworks, Determinants, and Research Challenges (2018-2024) - Fathurrohman, Yusuf Enril; Kontor, Enikő (Journal of Management and Business Review, 2026)
This study synthesizes current research on consumer behavior and purchase intention in the halal food sector by conducted a systematic literature review of 37 articles (2018-2024) from the Scopus database using the PRISMA approach. Results show that the TPB is the most frequently applied framework, often extended with additional variables. Key determinants of purchase intentions and decisions include TPB variables, religiosity, halal awareness, and halal certification. Despite these findings, the literature faces challenges such as small samples sizes, limited geographic coverage, over-reliance on TPB, and certification inconsistencies. The study contributes by consolidating current evidence on consumer behavior in the halal food sector and highlighting the pivotal roles of religiosity and halal awareness. Practically, findings guide businesses, policymakers, and marketers in designing targeted strategies, enhance consumer trust, and expanding halal food markets. Future research should adopt larger, more diverse samples, and cross-cultural analyses to address existing gaps.